2019
DOI: 10.1093/asj/sjz284
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting Provides Good Outcomes as a Soft-Tissue Replacement in Hemifacial Atrophy

Abstract: Progressive hemifacial atrophy, also known as Parry-Romberg syndrome (PRS), is a rare disease characterised by atrophy of the skin, subcutaneous tissues, cartilage and mimetic muscles of the hemiface. More severe cases lead to degeneration of the bony framework and can be accompanied neurologic and ophthalmologic complications, alopecia areata and changes in hair colour. The resultant asymmetry can have considerable psychological sequelae and treatment aims to reconstruct the soft tissue destruction and restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Oro-facial fibrosis is recognised as a cause of significant concern in SSc patients and yet there has been no effective treatment to target skin fibrosis. Emerging studies reporting clinical improvement after autologous lipotransfer are encouraging and support the use of this well-established surgical technique as a novel therapeutic approach in these patients [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . It is postulated that antifibrotic effects are mediated by adipose-derived stem cells (ADSCs).…”
Section: Methods and Designmentioning
confidence: 79%
See 1 more Smart Citation
“…Oro-facial fibrosis is recognised as a cause of significant concern in SSc patients and yet there has been no effective treatment to target skin fibrosis. Emerging studies reporting clinical improvement after autologous lipotransfer are encouraging and support the use of this well-established surgical technique as a novel therapeutic approach in these patients [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . It is postulated that antifibrotic effects are mediated by adipose-derived stem cells (ADSCs).…”
Section: Methods and Designmentioning
confidence: 79%
“…Autologous lipotransfer is a minimally invasive surgical technique that is used for correcting volumetric deficits and soft tissue, however is now finding a role in fibrotic conditions [9] , [10] . Our group and others have suggested that it may improve skin fibrosis in different conditions including hypertrophic scars, burns, radiation-induced fibrosis, lichen sclerosis, and hemifacial atrophy [11] , [12] , [13] , [14] . Autologous lipotransfer has been also reported in small cohorts of SSc patients with facial or hand involvement [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 95%